Manipulation of superparamagnetic bead through motion of domain wall - Chen, Jun Xiang (2015)
Precise manipulation and sensing of surface-functionalized superparamagnetic (SPM) beads are fundamental functions governing the development in fields such as Biotechnology, Nano-Chemistry and Nano-Medicine.1-4 Current technologies catering to these functions are commonly done using specialized equipment for each individual role. This led to the notion of integration of these functions into a single miniaturized device. This has been shown possible with recent findings on localized potential in ferromagnetic materials.4, 5 Studies have shown that stray field emitted from Domain Wall (DW) within ferromagnetic materials has the capability to generate potential well that can be used to attract SPM bead. Furthermore, DW can be driven along the material with the facilitation of an external magnetic field. Magnetostatic interaction between bead and domain wall will result in a force that drives bead along the material. Recent works demonstrated on structures that constrain magnetic beads to pre-defined patterned paths. The variety of track options was not present in these structures. This limitation was observed in drug discovery where effectiveness of chemotherapeutic drug is impeded by insufficient understanding of their means of action.2 Obtaining precise spatial manipulation over a large areas and control at single molecule level are also important for observing the dynamical interaction of single cells. This led to the inspiration of this work to construct structure that allows for variety of track options. This has been achieved using an array-of-semicircles structure. It was fabricated using lithography and sputtering techniques. A Software Reprogrammable Magnetic Quadruple (SRMQ) has been used to manipulate the magnetic bead. Results have shown that this structure provides more track options compared to previous works. Multiple magnetic beads manipulation simultaneously was also achievable using this structure. Aside from all these, this work has shown magnetic bead driven in an oscillatory motion on a circular ring that was not observed in previous works.